2006
DOI: 10.1038/sj.jcbfm.9600218
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 Receptor Knockout Mice Develop Lethal Status Epilepticus after Experimental Traumatic Brain Injury

Abstract: Adenosine, acting at A1 receptors, exhibits anticonvulsant effects in experimental epilepsy--and inhibits progression to status epilepticus (SE). Seizures after traumatic brain injury (TBI) may contribute to pathophysiology. Thus, we hypothesized that endogenous adenosine, acting via A1 receptors, mediates antiepileptic benefit after experimental TBI. We subjected A1-receptor knockout (ko) mice, heterozygotes, and wild-type (wt) littermates (n=115) to controlled cortical impact (CCI). We used four outcome prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(142 citation statements)
references
References 66 publications
6
130
2
1
Order By: Relevance
“…All KA-injected Adk-tg and A 1 R knockout mice died within the first three days after KA-injection and displayed excessive SE (Li et al, 2008). Again, Adk-tg and A 1 R knockout mice displayed striking similarity with regard to increased vulnerability to acute brain injury, consistent with earlier reports of lethal status epilepticus in A 1 R knockout mice induced by intrahippocampal kainate or traumatic brain injury (Kochanek et al, 2006).…”
Section: Adk-tg and A 1 R Knockout Mice Display Increased Ka-induced supporting
confidence: 87%
See 2 more Smart Citations
“…All KA-injected Adk-tg and A 1 R knockout mice died within the first three days after KA-injection and displayed excessive SE (Li et al, 2008). Again, Adk-tg and A 1 R knockout mice displayed striking similarity with regard to increased vulnerability to acute brain injury, consistent with earlier reports of lethal status epilepticus in A 1 R knockout mice induced by intrahippocampal kainate or traumatic brain injury (Kochanek et al, 2006).…”
Section: Adk-tg and A 1 R Knockout Mice Display Increased Ka-induced supporting
confidence: 87%
“…To further elucidate the downstream components of the adenosine / epileptogenesis pathways, in the present study we subjected A 1 receptor knockout mice to our paradigm of CA3-selective epileptogenesis and provide the following findings: We previously demonstrated that A 1 R activation is necessary to keep an epileptic focus localized . Likewise, traumatic brain injury in A 1 R knockout mice led to increased seizure spread and lethal status epilepticus (Kochanek et al, 2006). Here we demonstrate for the first time that A 1 R knockout mice develop focal spontaneous seizures in the absence of an epileptogenesis-precipitating injury.…”
Section: Downstream Effectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tonic activation of A 1 receptors by an endogenous tone of adenosine is believed to lead to long-distance A 1 receptor mediated inhibition and thus to mediate heterosynaptic depression (Manzoni et al, 1994). In regard to epilepsy, A 1 receptors, which have high expression levels in epilepsy-prone regions such as hippocampus (Fredholm et al, 2001), would thus be uniquely positioned to convey paracrine anticonvulsant functions of adenosine (Güttinger et al, 2005a;Güttinger et al, 2005b) and to prevent the spread of epileptogenic activity Kochanek et al, 2006).…”
Section: Adenosine a 1 Receptorsmentioning
confidence: 99%
“…The generation of mice with moderately reduced levels of ADK in brain rather than complete ADK deficiency seems to be essential, since several lines of evidence suggest that only small changes in ADK levels are permissible: (i) The homozygous disruption of ADK is lethal (Boison et al, 2002b); (ii) ADK is highly conserved in evolution (Spychala et al, 1996), suggesting that mutations are not easily tolerated; (iii) No mutations of human ADK are known in man (OMIM, Online Mendelian Inheritance in Man, Victor A. McKusick et al, Johns Hopkins University) indicating that most mutations are lethal; (iv) Excessive levels of ADK lead to severe deficits in A 1 R activation and to lethal status epilepticus or cell death after otherwise non-lethal triggers Kochanek et al, 2006;Li et al, 2007a;Pignataro et al, 2007b); (v) Inadequate levels of ADK in brain are expected to lead to a rise in adenosine to unacceptably high levels, with likely lethal consequences, e.g. central apnea and perinatal mortality induced by elevated adenosine (Montandon et al, 2006).…”
Section: Seizure Susceptibility In Adenosine Kinase Transgenic Micementioning
confidence: 99%